The Problems Associated with Public Prosecutors in Enforcing the Act Establishing District Courts and Criminal Procedure in District Courts, B.E. 2499 (1956) - Untharin, Pasit; Tuppawimol, Punnawit; Muangtham, Wanwipa (Ph.D. in Social Sciences Journal, 2025)
This research article aims to study and examine principles, and historical background related to criminal prosecution in district courts by public prosecutors; study and compare the legal measures related to criminal prosecution in district courts by public prosecutors in Thailand and other countries; analyze the challenges faced by public prosecutors in the criminal trial process in district courts in Thailand and other countries; and propose recommendations for amending legal measures related to criminal prosecution in district courts by public prosecutors in Thailand to ensure suitability and maximum effectiveness. Findings are as follows: criminal prosecutions in district courts by public prosecutors face challenges such as delays by investigating officers in forwarding case files to public prosecutors, delays in approving the prosecution of suspects, and delays in filing motions for defendants to compensate damages; public prosecutors in Thailand lack the authority to conduct investigations, whereas in other countries, public prosecutors have the power to investigate; the involvement of public prosecutors in the investigation process prevents delays in forwarding case files and allows them to specify the key issues to be investigated, ensuring that the evidence can be effectively presented during trial; the study recommends legal amendments to set clear deadlines for the submission of investigation files, grant the authority to approve prosecutions to Director General for Regional Public Prosecution 1-9 and the Director General of the Office of District Court Prosecution instead of the Attorney General, with a decision timeframe of one month, and require investigating officers to inform victims of their right to claim compensation under Section 44/1 of the Criminal Procedure Code before forwarding the case files to public prosecutors.